Post-Meiotic Intra-Testicular Sperm Senescence in a Wild Vertebrate - Hettyey, Attila; Vági, Balázs; Penn, Dustin J.; Hoi, Herbert; Wagner, Richard H. (PLOS ONE, 2012)
There is growing interest in sperm senescence, both in its underlying mechanisms and evolutionary consequences, because it can impact the evolution of numerous life history traits. Previous studies have documented various types of sperm senescence, but evidence of post-meiotic intra-testicular sperm senescence in wild animals is lacking. To assess such senescence, we studied within-season changes in sperm motility in the common toad (Bufo bufo), where males produce all sperm prior to the breeding season. We found that males exposed to experimentally induced re-hibernation at the start of the breeding season, that is to experimentally lowered metabolic rates, stored sperm of significantly higher motility than males that were kept under seminatural conditions without females throughout the breeding season. This finding indicates that re-hibernation slows normal rates of sperm ageing and constitutes the first evidence to our knowledge of post-meiotic intra-testicular sperm senescence in a wild vertebrate. We also found that in males kept in seminatural conditions, sperm motility was positively related to the number of matings a male achieved. Thus, our results suggest that post-meiotic intra-testicular sperm senescence does not have a genetically fixed rate and may be modulated by temperature and possibly by mating opportunities.